Deployment Strategies for Golden Rice in Bangladesh: A Study on Affordability and Varietal Choice with the Target Beneficiaries - Mohammad Chhiddikur Rahman; Md. Shajedur Rahaman; Mohammad Ariful Islam; Md. Imran Omar; Md. Abu Bakr Siddique (Bangladesh Rice Research Institute, 2021)
The sustainable development goals emphasized achieving food security and improved nutrition for all. As nothing is more important than health, all should have adequate basic nutrients to lead a healthy life. Vitamin A deficiency (VAD) is a major problem in large parts of the developing world. Apart from acute symptoms of eye problems, VAD also weakens the immune system, thus increasing the incidence and severity of infectious diseases. For adults, the implications can be serious too, especially for pregnant and lactating women. The most affected are the poor, whose diets are predominated by less nutritious staple foods on account of lacking purchasing power and limited awareness. `Golden Rice' has been developed through genetic engineering at Swiss and German universities. It is a new type of rice that contains `beta-carotene', which is converted into vitamin A inside the body as needed and gives the grain its golden color. It's grown just like ordinary rice and aims to provide 30-50% of the estimated average requirement for vitamin A. It could improve the vitamin A status of deficient food consumers, especially women and children in developing countries. Some optimists praise it as the solution to overcome malnutrition and VAD. It already has received biosafety approval and released in the Philippines and hopes to release in Bangladesh soon. Prior to the release, the healthier rice team aimed to draw a deployment strategy of golden rice in Bangladesh. Therefore, this study has been conducted to assess the affordability and varietal choice of the targeted beneficiaries in the specific regions of Bangladesh.
Keywords: 630; Golden rice; Deployment policy; Ex-ante; vitamin A deficiency; Bangladesh